Molecular and morphological characterization of Acanthamoeba isolated from corneal scrapes and contact lens wearers in Argentina (2017)
In this study, we describe the frequency of Acanthamoeba keratitis (AK) in patients that assisted in the Ophthalmology Department and determine the species/genotypes of free living amoebas (FLA) isolates. FLA from Corneal scrapes (CS) and contact lens (CL) wearers were studied by morphological and molecular characterization. A database was constructed with sociodemographic, clinical findings and history of use of CL variables. During January 2000 and September 2016 patients with corneal pathology admitted to the Ophthalmology Service of the University Hospital in Córdoba city, Argentina were included in the study. FLA were detected in 1.5% (11/739) and in 17% (11/65) of CS and CL analyzed respectively. FLA isolates from CL users evidenced an 80.9% of inappropriate lens maintenance, 4.8% (1/21) were not CL users that have been in contact with waters in outdoor environment and 14,3% (3/21) with no data about CL users. Acanthamoeba was confirmed in 100% and 82% of CS and LC respectively. The most frequent symptom associated with AK was red eye and photophobia. FLA from CS belonged to group II but 82% (9/11) and 18% (2/11) from CL belonged to group II and III respectively. T4 genotype and A. polyphaga species were detected in 100% of Acanthamoeba isolates. Poor CL hygiene practices, highlights the need for improved education about the severity of AK and consequences of improper CL hygiene. Genotype T4 detected in 100% of both CS and CL samples, consistently with previous findings indicating that this genotype is by far the most prevalent isolated from ocular infection. © 2017 Elsevier B.V.